Evaluación del Patrimonio Construido (Smithsonian Institution Scholarly Press, 2024)
This manual describes simple tests for evaluating the condition of built heritage and cultural monuments. The tests were selected for their simplicity and widespread availability, especially in countries where few institutions deal with the conservation of important buildings or monuments and where laboratories capable of the necessary analyses are scarce.